2019
DOI: 10.1002/ece3.5506
|View full text |Cite
|
Sign up to set email alerts
|

Future hydrological constraints of the Montseny brook newt (Calotriton arnoldi) under changing climate and vegetation cover

Abstract: The Montseny brook newt (Calotriton arnoldi) is a critically endangered amphibian species which inhabits a small 20 km2 holm oak and beech forest area in NE Spain. Calotriton arnoldi strictly lives in running waters and might be highly vulnerable to hydrological perturbations expected to occur under climate and vegetation cover changes. Knowledge about the potential response of the species habitat to environmental changes can help assessing the actions needed for its conservation. Based on knowledge of the spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
(73 reference statements)
0
3
0
Order By: Relevance
“…Recently, the stream hydrological response to climate change scenarios from IPCC and to land use changes was modelled in the context of LIFE‐Tritó project. The aim was to predict the vulnerability of the critically endangered Montseny newt ( Calotriton arnoldi ) to expected habitat changes in future scenarios (Ledesma et al, 2019). In this work, the combination of hydrological modelling, climatology and knowledge of the species ecology provided an example of the use of data gathering and processing to help in the management of an endangered species.…”
Section: Main Biogeochemical Resultsmentioning
confidence: 99%
“…Recently, the stream hydrological response to climate change scenarios from IPCC and to land use changes was modelled in the context of LIFE‐Tritó project. The aim was to predict the vulnerability of the critically endangered Montseny newt ( Calotriton arnoldi ) to expected habitat changes in future scenarios (Ledesma et al, 2019). In this work, the combination of hydrological modelling, climatology and knowledge of the species ecology provided an example of the use of data gathering and processing to help in the management of an endangered species.…”
Section: Main Biogeochemical Resultsmentioning
confidence: 99%
“…More recently, the stream hydrological response to climate change scenarios from IPCC and to land use changes was modeled in the context of LIFE-Tritó project. The aim was to predict the vulnerability of the critically endangered Montseny newt (Calotriton arnoldi ) to expected habitat changes in future scenarios (Ledesma et al 2019). In this work, the combination of hydrological modelling, climatology and species ecology knowledge provides an example of the use of data gathering to help in the management of an endangered species.…”
Section: Streamwater Chemistrymentioning
confidence: 99%
“…This research followed the small catchment approach developed at Hubbard Brook (Bormann et al 1979) and, sustained over several decades, has been instrumental in showing the responsiveness of forested ecosystems to atmospheric deposition changes (Avila and Rodà 2012;Bernal et al 2013;Avila et al 2020) and the uniqueness of stream N response to deposition in Mediterranean forests as compared to temperate forests (Templer et al 2022). The effects of forest management on (1) stream chemistry has been modelled (Neal et al 1995) and that of climate change on stream chemistry (Avila et al 1996) and on the habitat suitability for an endangered amphibian species as well (Ledesma et al 2019). Mineral dust, originated in North Africa (Avila et al 2007) has been shown to be an important contributor of nutrients and alkalinity to these forest ecosystems (Avila et al 1997(Avila et al , 1998.…”
Section: Introduction and Antecedentsmentioning
confidence: 99%